Pengaruh LKPD Berbasis Inkuiri Terstruktur untuk Meningkatkan Keterampilan Proses Sains Peserta Dididk Kelas VIII SMPIT Nurul Fikri - Reski Auliyah Basir; Salma Samputri; Sitti Rahma Yunus (Universitas Negeri Makassar, 2024)
This study aims to determine: 1) the level of science process skills scores of experimental and control class students Structured inquiry-based worksheets. 2) the improvement of students' science process skills through the application of structured inquiry-based worksheets in experimental and control classes. 3) the effect of the application of structured inquiry-based worksheets on the science process skills of 8th grade students of SMPIT Nurul Fikri. This type of research is a Quasi-Experiment with a research design using Nonequivalent Control Group Design. The population is all VIII grade students, 2023/2024 school year consisting of 4 classes with a total of 63 people. The sample was selected by purposive sampling, with 2 classes, namely Class VIIIB totaling 18 people as the experimental class and Class VIIIC totaling 22 people as the control class. The research instrument was a science process skills test question. Data collection was done by giving pretest and posttest. Data were analyzed with descriptive statistics and inferential statistics. Based on the results of the analysis, it was found that; 1) the level of science process skills of students in the experimental class before applying structured inquiry-based worksheets, was in the medium category with a score of 9.00 and after being applied was in the high category with a score of 12.88 while in the control class before applying conventional worksheets was in the medium category with a score of 10.22 and after being applied was in the high category with a score of 11.54. 2) the increase in science process skills of students who applied structured inquiry-based worksheets was in the medium category with an N-Gain of 0.35. 3) based on the results of inferential analysis that there is an effect of the application of structured inquiry-based worksheets on the science process skills of class VIII students at SMPIT Nurul Fikri.